PENGARUH PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Astriani, Nurullita; Dhana, Muhammad Bayu Al (Journal of Didactic Mathematics, 2020)
This study aims to determine the effect of think pair share type of cooperative learning on students' mathematical representation abilities. This research is a quasi-experimental research. The population in this study were all eighth-grade students of SMP Negeri 1 Pangkalan Susu. The samples in this study were 2 classes, namely class VIII-1 which was used as an experimental class and class VIII-2 was used as a control class. The instrument used was a test in the form of a description of the material Relations and Functions. From testing the hypothesis obtained tcount (2.135) > ttable (1.6715) means that Ho is rejected and Ha is accepted. This shows the influence of think pair share type of cooperative learning on students' mathematical representation ability.